Arterial damage and cognitive decline in chronic kidney disease patients. Issue 9 (14th July 2018) - Karasavvidou, Despina; Boutouyrie, Pierre; Kalaitzidis, Rigas; Kettab, Hakim; Pappas, Kosmas; Stagikas, Dimitrios; Antonakis, Nikolaos; Tsalikakis, Dimitrios; Elisaf, Moses; Laurent, Stephane
Abstract : In the general population aortic stiffening, assessed by carotid femoral pulse wave velocity (cf‐PWV), is associated with cognitive dysfunction (CO/DY). Data in chronic kidney disease (CKD) are limited. This study tests the hypothesis that large artery stiffness and microvascular damage in CKD patients are related to the damage of brain microcirculation reflected by impaired cognitive function. A cross‐sectional study enrolled 151 patients (mean age 58.4 years; 64.5% males; 44 patients with CKD stage 1; 47 with stage 2; 25 with stage 3; and 35 with stage 4). Cognitive impairment, assessed by the Mini Mental State Examination (MMSE), the Clock – drawing test (Clock‐test), and the Instrumental Activity of Daily Living (IADL), was considered as primary outcome. We measured systolic and pulse pressures at the brachial and aortic sites and cf‐PWV. Our patients revealed a significant linear deterioration in all the domains of cognitive function according to CKD stages. High values of cf‐PWV ( P = 0.029) and aortic pulse pressure (aPP) ( P < 0.026) were independent determinants of cognitive decline assessed by the MMSE. The present trial supports the hypothesis of an interaction between the kidney, large artery damage, central pressure pulsatility, and the injury of brain microcirculation. In clinical practice, cf‐PWV and aPP measurements may help to predict cognitive decline. Whether the reduction in aortic stiffness following an aggressive treatment translates into improved cognitive outcomes remains to be determined.